Human capital, economic growth, and inequality in China - James J. Heckman; Junjian Yi (Institute for the Study of Labor (IZA), 2012)
China's rapid growth was fueled by substantial physical capital investments applied to a large stock of medium skilled labor acquired before economic reforms began. As development proceeded, the demand for high skilled labor has grown, and, in the past decade, China has made substantial investments in producing it. The egalitarian access to medium skilled education characteristic of the pre-reform era has given rise to substantial inequality in access to higher levels of education. China's growth will be fostered by expanding access to all levels of education, reducing impediments to labor mobility, and expanding the private sector.
urn:nbn:de:101:1-201301189228
Keywords: I25; J24; O15; 330; education; human capital; economic growth; inequality; Bildungschancen; Bildungsinvestition; Wirtschaftswachstum; Entwicklung; China